2016
DOI: 10.1107/s2059798316006306
|View full text |Cite
|
Sign up to set email alerts
|

DNA polymorphism in crystals: three stable conformations for the decadeoxynucleotide d(GCATGCATGC)

Abstract: High-resolution structures of DNA fragments determined using X-ray crystallography or NMR have provided descriptions of a veritable alphabet of conformations. They have also shown that DNA is a flexible molecule, with some sequences capable of adopting two different structures. Here, the first example is presented of a DNA fragment that can assume three different and distinct conformations in crystals. The decanucleotide d(GCATGCATGC) was previously reported to assume a single-stranded double-fold structure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…To gain insight into the principles that govern the folding of NA structures and the interactions of NAs with both proteins and drug‐like molecules, NA have been intensively studied using a number of biophysical methods, including atomic‐resolution methods such as X‐ray diffraction and solution NMR spectroscopy. However, instead of providing a unique set of (quantitative) relationships between an NA sequence and its 3D geometry and/or the interactions profiles, these studies revealed that essentially all aspects of NA stereochemistry not only are a simple function of the NA primary sequence but are also modulated by chemical‐physical environmental factors, such as ionic strength, the nature of counterions, pH and water activity . The observation that the structure, dynamics and interactions of NAs might be strongly influenced by the subjectively chosen environmental conditions and experimental setups used for investigations indicated that the conventional in vitro methods of structural biology and biophysics, which are all abstracted from the native environmental context of a cell, must be used with caution when considering the physiological relevance of the structural and biophysical data on NAs.…”
mentioning
confidence: 99%
“…To gain insight into the principles that govern the folding of NA structures and the interactions of NAs with both proteins and drug‐like molecules, NA have been intensively studied using a number of biophysical methods, including atomic‐resolution methods such as X‐ray diffraction and solution NMR spectroscopy. However, instead of providing a unique set of (quantitative) relationships between an NA sequence and its 3D geometry and/or the interactions profiles, these studies revealed that essentially all aspects of NA stereochemistry not only are a simple function of the NA primary sequence but are also modulated by chemical‐physical environmental factors, such as ionic strength, the nature of counterions, pH and water activity . The observation that the structure, dynamics and interactions of NAs might be strongly influenced by the subjectively chosen environmental conditions and experimental setups used for investigations indicated that the conventional in vitro methods of structural biology and biophysics, which are all abstracted from the native environmental context of a cell, must be used with caution when considering the physiological relevance of the structural and biophysical data on NAs.…”
mentioning
confidence: 99%
“…Second, the interaction between these single stranded sticky ends leads to a predictable local structure-the Watson-Crick duplex-when programmed via complementary base pairs [18]. Sequence-specific structural variations that can lead to deviations in the Watson-Crick duplex [19,20], and a number of non-canonical DNA base pairing motifs that can compete with Watson-Crick base pairing [21][22][23][24], can be mitigated by careful sequence selection. Third, the association between DNA strands is a self-assembly process.…”
Section: Introductionmentioning
confidence: 99%